The Corporate Governance Landscape of Pakistan - Edited by Sadia Khan (Karachi Oxford University Press, 2017)
This book provides a comprehensive guide to the existing policy frameworks, principles, and practices of corporate governance in Pakistan today.
Include Graphs and Index
Keywords: Pakistan -- Corporate governance